Cartographic language: ways to express the subjectivity of geographical space - Costa, Christiane Fernanda da [UNESP]; Pezzato, Joao Pedro [UNESP] (Univ Fed Goias, Inst Estudos Socio-ambientais, 2016)
In this article, we present results of a Master thesis defended in 2015, where the research with the cartographic language expanding the available knowledge regarding the scholar cartographic studies, and their overlaps with the study of the locality were acknowledged. The data were obtained from ten meetings, with the completion of a didactic sequence, from the study of the surroundings; with fifty-eight students from two classrooms of 3rd year of primary school, from a public school in the municipality of Rio Clam, Sao Paulo, Brazil. Among the activities performed in the local study, we highlighted the productions resulting from an educational tour of the history of the municipality space formation, particularly emphasizing the State Forest Edmundo Navarro de Andrade (FEENA). Analysis of the records allows us to state that the study of the surroundings has provided the experience leases concerning the production of knowledge by the students, such as observation, description; establishing relationships and correlations, the production of conclusions and syntheses.
Keywords: cartographic language; elementary school; geography; State Forest Edmundo Navarro de Andrade